Effects of GLP-1 on counter-regulatory responses during hypoglycemia after GBP surgery. Issue 2 (August 2019) - Almby, Kristina E; Abrahamsson, Niclas; Lundqvist, Martin H; Hammar, Ulf; Thombare, Ketan; Panagiotou, Amalia; Karlsson, F Anders; Sundbom, Magnus; Wiklund, Urban; Eriksson, Jan W
Abstract : Objectives: The aim of the study was to explore the role of GLP-1 receptor activation on the counter-regulation and symptoms of hypoglycemia in subjects who have undergone gastric bypass surgery (GBP). Design: Experimental hyperinsulinemic–hypoglycemic clamp study. Methods: Twelve post-GBP subjects participated in a randomized cross-over study with two hyperinsulinemic, hypoglycemic clamps (glucose nadir 2.7 mmol/L) performed on separate days with concomitant infusions of the GLP-1 analog exenatide or with saline, respectively. Continuous measurements of metabolites and counter-regulatory hormones as well as assessments of heart rate variability and symptoms of hypoglycemia were performed throughout the clamps. Results: No effect of GLP-1 receptor activation on counter-regulatory hormones (glucagon, catecholamines, cortisol, GH) or glucose infusion rate was seen, but we found indications of a downregulation of the sympathetic relative to the parasympathetic nerve activity, as reflected in heart rate variability. No significant differences in symptom of hypoglycemia were observed. Conclusions/interpretation: Short-term exposure to a GLP-1 receptor agonist does not seem to impact the counter-regulatory hormonal and metabolic responses in post-GBP subjects during hypoglycemic conditions, suggesting that the improvement in symptomatic hypoglycemia post-GBP seen following treatment with GLP-1 receptor agonists may be mediated by mechanism not directly involved in counter-regulation.